Integrating Wheat Nucleolus Structure and Function: Variation in the Wheat Ribosomal RNA and Protein Genes - Appels, Rudi; Wang, Penghao; Islam, Shahidul (Frontiers in Plant Science, 2021)
We review the coordinated production and integration of the RNA (rRNA) and protein (RP) components of wheat cytoplasmic ribosomes in response to changes in genetic constitution, biotic and abiotic stress. The components examined are highly conserved and identified with reference to model systems such as human, Arabidopsis, rice, but have sufficient levels of change in their DNA and amino acid sequences which are suggested to form fingerprints or gene haplotypes that provide new markers to link genetic haplotypes with phenotype. Specifically, it is argued that populations of ribosomes within a cell can comprise distinct complements of rRNA and ribosomal proteins (RPs) to form units with unique functionalities which can become central in situations of stress where they may preferentially translate mRNAs coding for proteins better suited to contributing to survival of the cell. In model systems where this is well developed, the concepts build on the known variation in the translation machinery of the cell in response to stresses with respect to the engagement of initiation factors and elongation factors. The polyploid nature of wheat adds extra variation at each step of the synthesis and assembly of the rRNAs and RPs which can, as a result, potentially enhance its response to changing environments and disease threats.